Reconstructing the Legal Politics of Nominee Agreements in Direct Investment in Indonesia: Toward Beneficial Ownership Transparency and a Fair Investment Climate - Diwyacitta Nura Nugraha; Rofi Wahanisa; Suhadi Suhadi (Jurnal Dinamika Hukum, 2026)
The practice of nominee agreements in Foreign Direct Investment (PMA) in Indonesia is often used as a legal smuggling strategy by foreign investors to circumvent share ownership restrictions in the Negative Investment List (DNI). This phenomenon reflects the current investment legal policy (ius constitutum) which is ambivalent; on the one hand, it prohibits normatively, but on the other hand, it is weak in law enforcement, thus creating an unhealthy business competition climate (unfair competition) and potential losses to the country's economic sovereignty. This study aims to criticize the effectiveness of existing regulations and formulate an ideal legal political reconstruction to realize investment justice. This study is a normative legal research using a statutory approach (statute approach), a conceptual approach (conceptual approach), and a political-legal approach (political-legal approach). The results of the study indicate that the prohibition on nominee agreements in Article 33 of the Investment Law and Article 48 of the Limited Liability Company Law has not been effective due to the lack of an integrated oversight instrument for beneficial owners. Therefore, a reconstruction of legal politics (ius constituendum) is needed that shifts from a passive prohibition paradigm to an absolute transparency regime. The proposed reconstruction concept includes: (1) Formalization of the obligation to declare beneficial ownership explicitly in the law, accompanied by strict sanctions; (2) Implementation of the Nominee Amnesty mechanism as a restorative transitional solution; and (3) Harmonization of the cross-sectoral supervisory system that integrates data from the OSS, the Directorate General of AHU, and the PPATK